2016
DOI: 10.1101/cshperspect.a026039
|View full text |Cite
|
Sign up to set email alerts
|

p53 Isoforms: Key Regulators of the Cell Fate Decision

Abstract: It is poorly understood how a single protein, p53, can be responsive to so many stress signals and orchestrates very diverse cell responses to maintain/restore cell/tissue functions. The uncovering that TP53 gene physiologically expresses, in a tissue-dependent manner, several p53 splice variants (isoforms) provides an explanation to its pleiotropic biological activities. Here, we summarize a decade of research on p53 isoforms. The clinical studies and the diverse cellular and animal models of p53 isoforms (ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(185 citation statements)
references
References 119 publications
6
179
0
Order By: Relevance
“…Finally, recent data from the D122p53 mouse has shown that there is also cooperativity as D122p53 enhanced the survival of p53-mutant mice (25) and full-length p53 increased the ability of D122p53 to promote cell migration (16). This is consistent with the isoforms functioning in a complex network to determine cell fate outcomes (17).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Finally, recent data from the D122p53 mouse has shown that there is also cooperativity as D122p53 enhanced the survival of p53-mutant mice (25) and full-length p53 increased the ability of D122p53 to promote cell migration (16). This is consistent with the isoforms functioning in a complex network to determine cell fate outcomes (17).…”
Section: Introductionsupporting
confidence: 67%
“…Multiple studies have now shown that p53 isoforms have distinct functions and frequently contribute to diseases including cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Elevated expression of the D40p53 isoform has been associated with metastatic melanoma and triple-negative breast cancers (7,19).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, p53 has been found to encode a large number of isoforms2425. It has demonstrated that p53 isoforms can modulate p53 functions either synergistically or antagonistically26.…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts encode protein isoforms that differ from canonical p53 by the lack of amino-terminal domains (D40p53, lacking residues 1 -39; D133p53, lacking residues 1-132) or by alternative carboxyl-terminal domains ( p53b and p53g) (Courtois et al 2004;Khoury and Bourdon 2010;Marcel et al 2011). Although the precise functions of these isoforms is still poorly understood, there is strong experimental evidence that amino-terminally truncated p53 variants may counteract the suppressor functions of full-length p53 protein (reviewed in Marcel et al 2011; see also Joruiz and Bourdon 2016).…”
Section: Toward An Unbiased Somatic Tp53 Mutation Spectrummentioning
confidence: 99%